Exploring confidence in boys' elementary dance education - Anggraeni, Sri Wulan; Alpian, Yayan; Harmawati, Harmawati; Anggraeni, Winda (Intelektual Pustaka Media Utama, 2024)
This study explored low self-confidence in elementary school male students and strategies to overcome it. This study used a qualitative descriptive approach, focusing on 18 fifth grade students. Data collection methods included interviews, classroom observations, and self-confidence questionnaires. Data analysis followed the Miles and Huberman model (data reduction, data presentation, and conclusion drawing). The results showed that most male students lacked confidence in solo dancing but were confident in groups. The inhibiting factors included lack of previous experience, discomfort in front of peers, fear of judgment, lack of support and encouragement, and lack of practice and preparation. To overcome these issues, inclusive learning strategies, support, and a supportive environment are essential. Eliminating gender stereotypes in dance education is also important. The implications of this study underscore the need to create a positive and inclusive environment for male students to develop their confidence and interest in dance. It is expected that their participation and involvement in arts activities at school will increase.